Career Leadership Style in Preventing Disputes Between Students in Mawaridussalam Islamic Boarding School, Deli Serdang District - Nurhidayah Nurhidayah; Hasnun Jauhari Ritonga (Kusuma Negara Business School, 2023)
This study aims to determine the caregiver's leadership style in preventing disputes between female students at the Mawaridussalam Islamic Boarding School, Dli Serdang Regency. This research used a descriptive qualitative method which was carried out through field research. Data collection techniques in this study used semi-structured interviews and observation. The research data is based on primary data sources and secondary data sources. The technique of data analysis in this study is by doing data reduction, presenting data, then making conclusions. The results of this study indicate that the leadership style carried by caregivers at the Al Mawaridussalam Islamic Boarding School greatly determines the condition of female students, therefore caregivers play a very significant role in preventing disputes between female students. The leadership style of caregivers at the Al Mawaridussalam Islamic Boarding School links the concept of management in preventing disputes between female students at the Al Mawaridussalam Islamic Boarding School, Deli Serdang Regency, namely the caregiver regulates the course of moderation between female students by thinking about planning, namely the caregiver creates a series of concepts that aim to prevent female students from discord. In this case the caregiver leads the female students to engage in collaboration on certain activities in order to create friendship.